Struktur Komunitas Capung di Kawasan Wisata Curug Lawe Benowo Ungaran Barat - Herlambang, Alamsyah Elang Nusa; Hadi, Mochamad; Tarwotjo, Udi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Dragonflies have an important role for the stability of the ecosystem that is as predator and prey at the same time. The availability of food resources and optimal environmental conditions affect the species richness of dragonflies in the habitats. Reasearch on dragonfly comunity structure aims to find out the differences of community structure in each habitat type in the region of Curug Lawe Benowo. The research was conductet in 4 different stations which focus on species of dragonfly, amount of an individual species, habitats, environmental conditions, and the corellation between the variables. The method used is point count. The results showed that there are 19 dragonfly species which came from 7 different Family. The total number of individuals encountered from 4 stations is 205. The common species that can be found in all of the stations is Euphaea variegata. The level of diversity are medium, the level of evenness is fairly even. Similarity of species in any habitat types indicate that the habitats has a three kind of similarity levels that is fairly equal, less equal and not equal. Data analysis shows that there is a corellations between environmental conditions, and dragonfly species, affecting abundance and distributions of a dragonfly in the habitats, and can be used to describe dragonflies community structure in the region.Â Key words: Community structure, dragonfly, Curug Lawe-Benowo